Effects of a plant-derived biostimulant application on quality and functional traits of greenhouse cherry tomato cultivars. (July 2022) - Distefano, Miriam; Steingass, Christof B.; Leonardi, Cherubino; Giuffrida, Francesco; Schweiggert, Ralf; Mauro, Rosario P.
Graphical abstract: Highlights: The effects of a plant biostimulant (PB) on greenhouse cherry tomato were studied. Analysis of two clusters (2nd vs. 6th) ripening during different periods. Detailed profile of carotenoids and tocochromanols in tomatoes were reported. The PB promoted yield and all lipophilic antioxidants but depressed sugars. Stronger PB effects were noticed on 6th cluster (ripening in winter) Abstract: A greenhouse experiment was conducted to study the effects of the application of a plant-derived biostimulant (Bioup® TF) on fruit quality and composition of two clusters (cluster II and cluster VI) of the cherry tomato cultivars 'Eletta', 'Kaucana', and 'Top Stellina'. The biostimulant application promoted fruit yield by 12% (up to 1.3 kg m −2 in 'Kaucana') and increased the concentrations of important functional constituents like phytoene, γ-tocopherol and β-tocopherol by up to 16, 25, and 23%, respectively. Fruits from late-ripe cluster VI showed higher fruit weights, D-fructose, and total sugar contents than those from early-ripe cluster II (by 15, 7 and 5%, respectively), but reduced concentrations of acyclic carotenoids (phytoene and lycopene) and tocochromanols (mainly γ-tocopherol, −44%). 'Top Stellina' showed the highest responsiveness to the biostimulant, as particularly (all- E )-β-carotene, phytofluene, and γ-tocopherol concentrations increased, indicating a genotype-dependent effect of the treatment. However, fruits of all treated genotypes showed a contextual decrease in D-fructose and total sugars in response to the biostimulant (on average by 7 and 10%, respectively), indicating a metabolic load burdening the accumulation of lipophilic antioxidants in cherry tomatoes at the expense of their taste-related C pool.